MODERN METHODS OF DIAGNOSTICS AND COMPARATIVE DIAGNOSIS OF SEASONAL VIRAL DISEASES IN CHILDREN. - Noraliev Ismoiljon Abdullaevich (TADQIQOTLAR.UZ, 2024)
Annotation: This article discusses modern diagnostic methods and comparative approaches for identifying seasonal viral diseases in children. Emphasis is placed on innovative and traditional diagnostic tools, comparing their effectiveness, accuracy, and practicality. The study provides insights into the challenges and advancements in pediatric diagnostics, ultimately aiming to enhance early detection and management of these prevalent illnesses.